The role of shockwaves in the enhancement of bone repair - from basic principles to clinical application. (June 2021) - Mittermayr, Rainer; Haffner, Nicolas; Feichtinger, Xaver; Schaden, Wolfgang
Highlights: Recent experimental findings suggest mechanotransduction as the underlying mechanism of shockwave therapy Only limited but successful studies are available on acute fractures treated with shockwaves High clinical efficacy is evident in delayed or non-healing fractures without undesirable side effects Abstract: Extracorporeal shockwave therapy is a treatment modality, originally introduced into the clinic as lithotripsie, which has also been successfully used in the last two decades in the non-invasive treatment of delayed or non-healing fractures. Initially, the mechanism of action was attributed to microfracture-induced repair, but intensive basic research has now shown that the shockwave generates its effect in tissue via mechanotransduction. Numerous signal transduction pathways have already been demonstrated, which in their entirety trigger an endogenous regeneration process via cell proliferation, migration and differentiation. Clinically, these shockwave-conveyed biological signals support healing of acute, delayed and non-union fractures. The attainable outcome is comparable to surgery but avoiding an open approach with associated potential complications. These advantageous properties with a clearly positive cost-benefit ratio make shockwave therapy a first line treatment in delayed and non-union fractures.